Ethnic differences in infant feeding practices and their relationship with BMI at 3 years of age – results from the Born in Bradford birth cohort study. Issue 10 (28th May 2014) - Santorelli, Gillian; Fairley, Lesley; Petherick, Emily S.; Cabieses, Baltica; Sahota, Pinki
<x content-type="archive" xml:space="preserve">Abstract</x> The present study aimed to explore previously unreported ethnic differences in infant feeding practices during the introduction of solid foods, accounting for maternal and birth factors, and to determine whether these feeding patterns are associated with BMI at 3 years of age. An observational study using Poisson regression was carried out to investigate the relationship between ethnicity and infant feeding practices and linear regression was used to investigate the relationship between feeding practices and BMI at 3 years of age in a subsample of 1327 infants in Bradford. It was found that compared with White British mothers, mothers of Other ethnicities were less likely to replace breast milk with formula milk before introducing solid foods (adjusted relative risk (RR) – Pakistani: 0·76 (95 % CI 0·64, 0·91), Other South Asian: 0·58 (95 % CI 0·39, 0·86), and Other ethnicities: 0·50 (95 % CI 0·34, 0·73)). Pakistani and Other South Asian mothers were less likely to introduce solid foods early ( < 17 weeks) (adjusted RR – Pakistani: 0·92 (95 % CI 0·87, 0·96) and Other South Asian: 0·87 (95 % CI 0·81, 0·93)). Other South Asian mothers and mothers of Other ethnicities were more likely to continue breast-feeding after introducing solid foods (adjusted RR – 1·72 (95 % CI 1·29, 2·29) and 2·12 (95 % CI 1·60, 2·81), respectively). Pakistani and Other South Asian infants were more likely to be fed sweetened foods (adjusted RR – 1·18 (95 % CI 1·13, 1·23) and 1·19 (95 % CI 1·10, 1·28), respectively) and Pakistani infants were more likely to consume sweetened drinks (adjusted RR 1·72 (95 % CI 1·15, 2·57)). No association between infant feeding practices and BMI at 3 years was observed. Although ethnic differences in infant feeding practices were found, there was no association with BMI at 3 years of age. Interventions targeting infant feeding practices need to consider ethnicity to identify which populations are failing to follow recommendations.